Perkembangan Ekonomi Masyarakat Transmigrasi Desa Air Terang Kecamatan Tiloan Kabupaten Buol - Anggraini, Olviana; Hamid, Abdul (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2024)
The aim of this research is to describe the initial process of incoming transmigration and the economic development of transmigration communities. This research uses field research with a qualitative descriptive approach. Data collection techniques use observation, interviews and documentation. The results of research on the economic development of the transmigration community in Air Terang Village, Tiloan District, Buol Regency, are as follows: First, the initial process of entering the transmigration community. Second, changes in life in terms of the economy of the transmigration community have experienced many developments in terms of the economy, the community can be said to be prosperous in terms of quality of life and material aspects, such as; quality of house, food. From aspects of life such as: land owned has increased, wealth assets, as well as private and public facilities that support the activities and needs of the community in Air Terang Village, Tiloan District, Buol Regency.